Impact of gout on the risk of atrial fibrillation. (17th December 2015) - Kuo, Chang-Fu; Grainge, Matthew J.; Mallen, Christian; Zhang, Weiya; Doherty, Michael
Abstract : Objectives. To examine the risk of atrial fibrillation (AF) at the time of first diagnosis of gout compared with matched controls and to follow incident gout patients and their matched controls after diagnosis to compare their subsequent risk of AF. Methods. From the UK Clinical Practice Research Data-link, 45 378 incident gout patients and 45 378 age-, sex-, practice-, registration year- and index year-matched controls were identified. Index dates were initial diagnosis date for gout patients and their matched controls. The risk of AF at diagnosis [odds ratios (ORs), using conditional logistic regression] and after the diagnosis of gout [hazard ratios (HRs), using Cox proportional models] were estimated, adjusted for BMI, smoking, alcohol consumption, ischaemic heart disease, heart failure, heart valve disease, hyperthyroidism and other comorbidities and medications. Results. The prevalence of AF at index date in gout patients (male, 72.3%; mean age, 62.4 ± 15.1 years) was 7.42% (95% CI 7.18, 7.66%) and in matched controls 2.83% (95% CI 2.67, 2.98%). The adjusted OR (95% CI) was 1.45 (1.29, 1.62). The cumulative probability of AF at 1, 2, 5 and 10 years after index date was 1.08, 2.03, 4.77 and 9.68% in gout patients and 0.43, 1.08, 2.95 and 6.33% in controls, respectively (log-rank test, P < 0.001). The adjusted HR (95% CIs) was 1.09 (1.03, 1.16). Conclusion. This population-based study indicates that gout is independently associated with a higher risk of AF at diagnosis and the risk is also higher after the diagnosis.